Editorial (Altre Modernità, 2018)
Language and Discourse in Social Media: New Challenges, New Approaches.by Massimiliano Demata, Dermot Heaney and Susan C. Herring TEXTS BY: Michael S. Boyd, Paola Catenaccio, Michelangelo Conoscenti, Giuliana Elena Garzone, Ilaria Moschini, Anna Franca Plastina, Alessandra Rizzo, Marianna Lya Zummo